Factors Influencing Farmers’ Knowledge of Artificial Insemination in Beef Cattle Production Systems - Dede Aprylasari; Dinar Anindyasari; Putri Daulika (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
Artificial insemination (AI) enhances beef cattle productivity and genetic quality, yet its success in smallholder systems depends on farmers’ technical knowledge, especially estrus detection and insemination timing. This study examined farmers’ knowledge of AI, factors influencing that knowledge, and related capacity-building strategies. An exploratory explanatory survey was conducted with 40 purposively selected beef cattle farmers involved in AI programs in North Samarinda, East Kalimantan. Farmers’ knowledge was measured using indicators covering AI concepts, estrus signs, insemination timing, and reproductive management. Data were analyzed using descriptive statistics, multiple linear regression, and SWOT analysis. Results showed that farmers’ knowledge was generally good to very good, although weaknesses remained in estrus detection and insemination timing. Non-formal education significantly improved knowledge, while longer farming experience had a significant negative effect. Farming role was not significant. SWOT results supported SO strategies, prioritizing non-formal education, technology-based extension, and continuous mentoring.